19.8k views
2 votes
What are the roots of the equation X squared plus 6X -9 equals zero?

2 Answers

2 votes

Answer:

x = -3 + 2√3 and

x = -3 - 2√3)

Explanation:

x² + 6x - 9 = 0 can be solved in a variety of ways. Here I'll "complete the square" to solve for x:

x² + 6x - 9 = 0 can be re-written as x² + 6x + 9 - 9 - 9 = 0. To do this, we identify the coefficient of x (which is 6), halve it (obtaining 3), square the result (obtaining 9), and then add and then subtract this result (9) between 6x - 9.

Simplifying x² + 6x + 9 - 9 - 9 = 0 results in:

(x + 3)² = 18

Taking the square root of both sides, we get:

x + 3 = ±√18) = ±3√2

Solving this for the two roots, we get:

x = -3 + 2√3 and

x = -3 - 2√3)

User Peit
by
5.9k points
3 votes

Answer: try using desmos.com

Explanation:

User Glenneroo
by
5.9k points